The Role Of Nasya (Nasal therapy) With Kashaya Paana(Decoction) By Rasna- Bala-Ashwagandha Sadhita Taila And Kashaya In The Management Of Cervical Degenerative Disc Disease W.S.R To Vishwachi. - Majumder, Alpana; Mahapatra, P B Kar (International Research Journal of Ayurveda & Yoga, 2021)
Introduction-Nowadays Degenerative disc disease is a common term in the medical science and usually found in Cervical or Lumber region. Degenerative disc disease is not a disease; it is a process of degeneration of discs, located in spinal cord. When degeneration develops in the cervical spine, mostly at C5-C6 level, Cervical degenerative disc disease occurs. Dull ache, sharp pain, crepitus in neck movement, numbness, weakness etc. are the clinical features of this disease. In Ayurveda, it may be comparable to the disease Vishwachi. (cervical spondylosis). It is one of the vataja nanatmaja (musculoskeletal and neurological disorder )characterized by Ruk (pain), Stambha (Stiffness), Toda (throbbing pain), Karmakshaya (loss of deeds) and daurbalya (weakness) of the bahu pristha (upper limb) etc. It is mainly of two types; Vataja and Vata-Kaphaja. No such effective remedy is found in other medical science except surgery to treat this disease. Hence, to find a safe and effective remedy for this illness, Nasya (nasal therapy) and Kashayam (decoction) have been chosen. Method-Total 18 patients of Vishwachi were selected from the OPD of I.P.G.A.E & R at S.V.S.P Hospital considering the inclusion and exclusion criteria. Nasya (Nasal therapy) with Rasna-Bala-Aswagandha taila and kashayam (Decoction) prepared with Rasna-Bala-Ashwagandha were given to them for 21 days. Observation- Very significant result was found in all signs and symptoms. Conclusion: The both treatment regimen showed the good efficacy to treat this disease.